(untitled) (Takwil: Journal of Quran and Hadith Studies, 2023)
There are pros and cons from scholars regarding Allah’s prohibition when asking for a candidacy position in a campaign for political office. This difference has been caused by the arguments in the Qur’an and al-Sunnah which prohibit or allow candidacy. Candidates can be justified if they have sufficient capacity, capability, and acceptability, as well as genuine motives to seek the pleasure of Allah and serve the public interest, not for personal gain or to the detriment of society. This study examines the hadith about "asking for a leadership position" with the Ma’anil hadith approach in library research. Data was collected from various hadith books and hadith syarah books. then Takhrij al-hadith is carried out to determine the quality of hadith, and understanding of hadith is analyzed using textual and contextual approaches. The results of the research show that all hadiths that prohibit asking for leadership positions have a high level of authenticity and can be used as evidence. Textually, the prohibition indicates that asking for a position will result in regret, and leadership positions are only given to those who meet certain requirements, not by asking. However, contextually, this prohibition may change according to the situation and conditions when running for office. Thus, from haram can be makruh, mubah, and so on.